Theoretical model of jihadi management in development documents of The education system of the Islamic Republic of Iran - Zohreh musazadeh; fereshteh moghadam; Sousan Keshavarz (علوم تربیتی از دیدگاه اسلام, 2022)
The present study aims to identify the theoretical model of Jihadi management in the development documents of the educational system of the Islamic republic of Iran. This research is qualitative and was conducted with the oretical approach and using Strauss and Corbin method(1990). The statistical population of the current study in the department of Jihadi management, including books, articles, jurnals, theses and all documents related to the Jihadi management area. In addition, in the field of evolutionary documents, the oretical fundamentals of fundamental change in theofficial education and public education system of the republic Islamic of Iran(1390), national curriculum of the Islamis republic of Iran(1391) and the document on the fundamentals transformation of the education system(1390) were included. Sampling is a purposeful type, In order to validate the findings of the research.The findings of this study are classified according to six categories. The category of jihadi education(the central category) Consists of subsections of jihadi education objectives, jihadi education principles, characteristics of the Jihadi educated generation and Jihadi belief. The category of the causal conditions is formed from faith in the original source, the facts of existence and the definitive sovereignty of divine traditions. The category of intervening conditions is comprised of a subcategory against impediment and hostility. The category of field is formed from subcategories Jihadi construction, Jihadi relations and elements of Jihadi education. The category of strategies consisting of 13 subcategories of Regular exaltation, ….The category of result includes educating the person of Saleh, cultivating the society of Saleh, establishing a new Islamic civilization and realizing the Tayyebeh life. The components of Jihadi management in development documents can be presented in the form of a paradigmatic Jihadi management modle.